Are Peasant Households Feasible in Terms of Policy? : The Debate on the Future of Semi-Subsistence Households in Ukraine - Koblianska, Inna; Pasko, Oleh; Hordiyenko, Mykola; Yarova, Inessa (Eastern European Countryside, 2024)
The paper provides an analysis of semi-subsistence farming in Ukraine during the period 2008–2018, with a special focus on policy towards peasant households, and its feasibility. Ukraine currently has several strategic documents that set the vectors for regulating the development of the industry. The current policy on the strategic development of agriculture, rural areas, and support for farming is found to be chaotic and inconsistent. The paper confirms the thesis regarding the low economic efficiency of natural farming, and given the specific weight of households in the production of certain types of food, emphasises that public costs for ensuring the country’s food security are thus fairly high. The overall identified trends in the Ukrainian countryside are a) the reduction of land size, naturalisation of economic activity and reduction of market activity (farms, as a rule, keep cattle, poultry and bees, although the safety and quality of livestock products produced in such farms is rather dubious); and b) the enlargement of individual peasant households and their focus on commodity production of agricultural products (mainly crops), with the simultaneous distortion of reported production volumes and, accordingly, tax evasion...............